2020
DOI: 10.3390/app10072280
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Industrial Heat Treatment and Barrel Finishing on the Mechanical Performance of Ti6Al4V Processed by Selective Laser Melting

Abstract: Additive manufacturing is now capable of delivering high-quality, complex-shaped metallic components. The titanium alloy Ti6Al4V is an example of a printable metal being broadly used for advanced structural applications. A sound characterization of static mechanical properties of additively manufactured material is crucial for its proper application, and here specifically for Ti6Al4V. This includes a complete understanding of the influence of postprocess treatment on the material behavior, which has not been r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…When the barrel rotates, the charge is moved upward until a critical angle is reached; therefore, a layer called the active layer slides down, resulting in a relative velocity between parts and media, generating a delicate abrasion and microremoval of material [28]. Fixturing of the parts during the process is not required; hence, this process is suitable for components with a variety of sizes, shapes (also complex), and materials, such as AM components [39]. The main BF process parameters are the filling percentage and the rotational speed [40].…”
Section: Secondary Finishingmentioning
confidence: 99%
“…When the barrel rotates, the charge is moved upward until a critical angle is reached; therefore, a layer called the active layer slides down, resulting in a relative velocity between parts and media, generating a delicate abrasion and microremoval of material [28]. Fixturing of the parts during the process is not required; hence, this process is suitable for components with a variety of sizes, shapes (also complex), and materials, such as AM components [39]. The main BF process parameters are the filling percentage and the rotational speed [40].…”
Section: Secondary Finishingmentioning
confidence: 99%
“…Nalli et al [80] investigated the barrel finishing and heat treatment effect on the mechanical properties of Ti-6Al-4V samples manufactured through SLM. For that, some specimens were heat-treated with distinct temperatures (482 • C, 704 • C, 788 • C, and 800 • C) and holding times (3 h, 4 h, 5 h, 6 h, 8 h, and 10 h).…”
Section: Heat Treatmentsmentioning
confidence: 99%
“…They also found that surface quality was enhanced by ACBF, while shot peening improved mechanical properties because induced compressive residual stresses improve micro and macro defects. Nalli et al [26] worked on the effect of process parameters of ACBF on dimensions and tensile behaviours of Ti-6Al-4 V parts. The results showed that the surface quality improved by increasing rotational speed while time was found as another important factor in this process by Boschato et al [27].…”
Section: Introductionmentioning
confidence: 99%